Pluralisme di Puja Mandala Nusa Dua Bali sebagai Destinasi Pariwisata Religi - I Gede Pasek Mancapara (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2018)
Advancement in technology, information, transportation, and communication today is often mentioned by sociologists as a large village of the world village, consequently a region becomes very diverse or heterogeneous, and multicultural, thus encouraging the interaction, cooperation, accommodation, and acculturation between individuals or various groups of the pluralistic society. Differences in cultural, ethnic, economic, racial and religious backgrounds can lead to tensions or even conflict. On the other hand, the constructivist makes these differences as a positive thing. Nowadays, pluralism that occurred in Indonesia, which as amulticultural country still occurs and sustains the realization of the Unitary State of the Republic of Indonesia based on the state ideology, namely Pancasila. In addition to creating a harmonious state among religious people, or between religious communities and the government, on the one hand it brings a positive impact to the image of the country as a consideration of tourists to visit Indonesia as a tourist destination with consideration of safety and comfort. That is what is trying to show in Puja Mandala as a religious tourism destination in one of the provinces of Indonesia, that is in Bali Province. The existence of a multiculturalpolitics of the government that tried to be dissected through the theory of ideology Louis Althusser and pluralism that occurred there dissected through the theory of Consensus Emile Durkheim. So it is known that through the hegemony of thegovernment with the imaginary ideology of the Minister of Tourism Post and Telecommunications at that time Joop Ave as a political form for the development of Indonesia as a whole, until the realization of the imaginary ideology in the real existence in the field until the realization of Puja Mandala development in Nusa Dua Bali as religious tourism destinations, to realize the development of Indonesia as a whole, to facilitate tourism in the area of ITDC in particular and the surrounding community as a place of worship, as well as become one of its own attraction for tourists considering the building is designed with magnificent and illustrates the harmony and trilogy of religious harmony in Puja Mandala precisely in Bali as part of the Unitary State of the Republic of Indonesia.